Waterfall Forest Environment Regulates Chronic Stress via the NOX4/ROS/NF-κB Signaling Pathway - Zhu, Zixin; Zhao, Xueke; OuYang, Qiuyue; Wang, Yinghui; Xiong, Yan; Cong, Shuo; Zhou, Mingyu; Zhang, Manman; Luo, Xinhua; Cheng, Mingliang (Frontiers in Neurology, 2021)
Forest therapy has been proven to have beneficial effects on people with depression and anxiety. However, it remains unknown whether the waterfall forest environment (WF) affects physical and psychological health of patients with chronic fatigue and how the WF regulate chronic stress. We investigated the effect of the WF on chronic fatigue and the molecular mechanism by which the WF regulates chronic stress. Twenty-four patients with chronic fatigue were randomly divided into two groups: the WF and the urban (U) group. Scores on Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD) and Fatigue Scale-14 (FS-14) were evaluated before and after environmental intervention. Detection of inflammatory factor levels and immunological analysis were also performed. In addition, the chronic stress rat model was constructed and the NOX4/ROS/NF-κB signaling pathway was investigated. waterfall forest environment. Twenty-four patients with chronic fatigue. The WF group showed a significant decrease in FS-14, HAMA and HAMD scores compared with the U group. The expression levels of glutathione peroxidase and superoxide dismutase were remarkably higher in the WF group than that in the U group. However, the expression levels of malondialdehyde and inflammatory factors (IL-1β, TNF-α, IL-6 and IL-10) were remarkably decreased after the intervention of the WF. In addition, the WF reduced the liver damage caused by chronic stress in rats by inhibiting the NOX4/ROS/NF-κB signaling pathway. The WF had a positive effect on immune enhancement and physical and psychological health in patients with chronic fatigue, and might inhibit chronic stress by regulating the NOX4/ROS/NF-κB signaling pathway.